Pengaruh kondisi fumigasi terhadap efektifitas pewarnaan dan keawetan kayu hutan rakyat - Istie Sekartining Rahayu; Esti Prihatin (Institut Pertanian Bogor, 2009)
Indonesian log consumption average in 1999-2004 was about 40 million cubic meter per year. Far above the capacity of natural forest to supply wood demand which was only 6.9 million cubic meter per year and only 5 million cubic meter per year from plantation forest. Now community forest has been managed well based on commercial orientation to fullfill the needs of forest products. Recently community forest is known as realible wood producer for furniture such as rubber wood (Hevea brasiliensis), Maesopsis (Maesopsis eminii), Jeunjing (Paraserianthes falcataria), Durian (Durio spp.), Jackfriut (Arthocarpus sp). However those woods have low appearance quality (pale colours and ununiform, texture not attractive). Thus they need some treatments to enhance their appearance, one of them by fumigation. The purpose of this researh are to gain optimalize fumigation condition (combination between amonia volume and time of fumigation) to have wood stain that resistance from weathering and to analyze durability of fumigation wood against Cryptotermes sp attack. The treatments were fumigation by 2, 4, 6 litre of amonia for 1, 2, 3 days. Those treatments were applied on 5 wood species (mahagony, jackfruit, rambutan, menteng and mindi). The results of this research showed that fumigation treatments have effects only on jackfruit, mahagony, rambutan. They did not have effects on menteng and mindi. Because the difference of tanin content between woods, made every wood had different reaction to fumigation (amonia). Based on comparison of all treatments quantitatively showed the most darkened colour of jackfruit was resulted by fumigation by 4 litre amonia for 3 days, mahagony was fumigation by 6 litre amonia for 2 days and rambutan was fumigation by 4 liter amonia for 2 days. Weathering resistance resulted all wood species did not resist to weathering or their colour fade away. Wood fumigation durability showed 100 % mortality of Cryptotermes sp (on jackfruit, mahagony and menteng), on the other hand mindi showed 83 % and rambutan 89% mortality of Cryptotermes sp.